2020
DOI: 10.31584/jhsmr.2020731
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barrier in Accessing Emergency Medical Services of Ethnic Groups in the Highlands of Chiang Rai Province, Thailand

Abstract: Objective: To explore the barriers of accessing emergency medical services among several ethnic groups, including the Hmong, Lisu, Lahu and Akha people. Material and Methods: The qualitative study was conducted to interview 43 participants, including the Akha, Lahu, Lisu and Hmong people. Purposive sampling was used to select participants for in-depth interviews, from February to March, 2019. The data were analyzed using content analysis. Results: The results show that the barriers of using emergency medical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The study focused on research published in Thailand's EMS database of Scopus. After collecting the results, there were 25 relevant articles which were found to be in accordance with the objectives of the study [6], [7], [8], [9], [10], [11], [12] [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30]. Most of the articles study pre-hospital operations, both in terms of personnel working, budget used, and the effects on the patients' outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The study focused on research published in Thailand's EMS database of Scopus. After collecting the results, there were 25 relevant articles which were found to be in accordance with the objectives of the study [6], [7], [8], [9], [10], [11], [12] [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30]. Most of the articles study pre-hospital operations, both in terms of personnel working, budget used, and the effects on the patients' outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous Thai studies revealed that the provision of healthcare services for these hill tribe people is inferior to that of other social groups. [7][8][9][10][11][12] Poverty appears to be a significant barrier to care access in communities with fewer healthcare providers and hospitals. Most hill tribe people live in poverty and have poorer access to healthcare.…”
Section: Pacific Rim Int J Nurs Res • October-december 2023mentioning
confidence: 99%
“…11,14 This causes many of them to have limited access to healthcare services. Some studies have focused on the barriers to accessing emergency medical services of hill tribe people, 12 the association between race/ethnicity and IFT, 15 and the opinion of health providers about IFT in rural areas. 5 Understanding how hill tribe people and healthcare providers (HCPs) viewed the current EMCs and IFT is necessary for developing context-specific IFT for them.…”
Section: Pacific Rim Int J Nurs Res • October-december 2023mentioning
confidence: 99%
“…4 These inequities in health research could significantly impact health policies, national and global programs, and the delivery of appropriate, acceptable, and scalable health services, through hindering access to crucial information related to health. 5 In this article, "dominant language" refers to the official or formal language of a specific setting or the language spoken by most people in that setting. In contrast, "minor language" refers to any non-dominant language or language spoken by a small fraction of people in the same setting.…”
mentioning
confidence: 99%
“… 4 These inequities in health research could significantly impact health policies, national and global programs, and the delivery of appropriate, acceptable, and scalable health services, through hindering access to crucial information related to health. 5 …”
mentioning
confidence: 99%